Relationship between bruxism and temporomandibular disorders in patients with psychiatric disorders: a systematic literature review (Research, Society and Development, 2023)
The following scientific article explores the relationship between bruxism, temporomandibular disorder (TMD), and conditions such as depression and anxiety. The aim of this study was to determine the prevalence of TMD in patients with psychiatric disorders and investigate the impact of these disorders on oral health and prognosis. Several studies were reviewed to examine this relationship, providing conflicting results in their conclusions. While some studies have found an association between psychiatric disorders and bruxism/TMD, others did not find a significant association. Psychological factors may influence both conditions, but the results vary depending on the study analyzed. Therefore, the relationship between these conditions is complex and requires further investigation for a complete understanding. The development of treatment protocols for these conditions should involve multidisciplinary professionals such as dentists, doctors, and psychologists in order to address the physical and psychological aspects involved. This integrated approach can help improve the prognosis and well-being of patients facing these problems together. It is important to emphasize that further research is needed to clarify the relationship between bruxism, TMD, and psychiatric disorders, as well as to develop effective and personalized interventions. Therefore, future studies in this area are essential to guide treatment and provide better therapeutic alternatives.